2016
DOI: 10.1186/s11671-016-1512-8
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Functionalized Fluorescent Silica Nanoparticles for Highly Sensitive Detection of Leukemia Cells

Abstract: A simple, highly sensitive method to detect leukemia cells has been developed based on aptamer-modified fluorescent silica nanoparticles (FSNPs). In this strategy, the amine-labeled Sgc8 aptamer was conjugated to carboxyl-modified FSNPs via amide coupling between amino and carboxyl groups. Sensitivity and specificity of Sgc8-FSNPs were assessed using flow cytometry and fluorescence microscopy. These results showed that Sgc8-FSNPs detected leukemia cells with high sensitivity and specificity. Aptamer-modified F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…These results reflect the established ability of Sgc8 aptamer to target leukemia cells [20]. Sgc8 recognizes PTK-7 on the surface of CEM cells [18], recruiting nanoparticles to the surface and thereby making their uptake more efficient [23]. Our results suggest that Sgc8-MSN/Dox may target PTK-7-expressing cancer cells at primary as well as secondary sites or in circulation, making it useful for controlling metastasis.…”
Section: Dox Release From Sgc8-msn/dox In Vitrosupporting
confidence: 71%
See 1 more Smart Citation
“…These results reflect the established ability of Sgc8 aptamer to target leukemia cells [20]. Sgc8 recognizes PTK-7 on the surface of CEM cells [18], recruiting nanoparticles to the surface and thereby making their uptake more efficient [23]. Our results suggest that Sgc8-MSN/Dox may target PTK-7-expressing cancer cells at primary as well as secondary sites or in circulation, making it useful for controlling metastasis.…”
Section: Dox Release From Sgc8-msn/dox In Vitrosupporting
confidence: 71%
“…We have designed a Sgc8 aptamer-modified fluorescent silica nanoparticles system (Sgc8-FSNPs) for detecting leukemia cells with high sensitivity and specificity, which prove useful not only for the diagnosis of leukemia but also for the targeted delivery of anti-leukemia drugs [18]. Based on this work, in the present study, we encapsulated doxorubicin (Dox) in MSNs, which we decorated with Sgc8 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao and colleagues developed aptamer-modified fluorescent silica NPs (FSNPs) by conjugating amine-labeled Sgc8 aptamer to carboxyl-modified FSNPs via amide coupling to detect leukemia cells. 26 They assessed the sensitivity and specificity of Sgc8-FSNPs using flow cytometry and fluorescence microscopy. The results showed that Sgc8-FSNPs could be used to accurately detect leukemia cells with high sensitivity, which indicated that Sgc8-FSNPs were a highly sensitive tool for specific detection of leukemia cells.…”
Section: Use Of Aptamers In Theranosticsmentioning
confidence: 99%
“…88 Fluorescent SiO 2 NPs can also be conjugated to an aptamer for CTC detection. One detection method of leukemia cells using aptamer-modified fluorescent SiO 2 NPs was presented by Tan et al 89 Due to selection of specific aptamers, this method could be adaptable to other types of cancer. Additionally, aptamer-NP conjugation can be advanced for drug-delivery applications.…”
Section: Magnetic-optical Bifunctional Nanoparticlesmentioning
confidence: 99%